Effect of ripening on in vitro digestibility and structural characteristics of plantain (Musa ABB) starch. (August 2019) - Bi, Yu; Zhang, Yayuan; Gu, Zhengbiao; Cheng, Li; Li, Zhaofeng; Li, Caiming; Hong, Yan
Abstract: This study focused on the effect of ripening on in vitro digestibility and the multi-scale structural characteristics of plantain starch. It was shown that the RS content of plantain starch gradually decreased during ripening process, while RDS and SDS contents increased. Scanning electron micrographs showed the layer-by-layer degradation of the surfaces of starch granules. The transformation from CB -type to CA -type crystalline structure of starch was revealed by wide angle X-ray diffraction patterns. Relative crystallinity, IR ratio 1045/1022 and the apparent amylose content all decreased with increasing maturity. Meanwhile, branched chain length distributions of amylopectin indicated that the content of short chain increased and that of long chain decreased, leading to the changes of digestion performance. In addition, the serious damage to amorphous region in semi-crystalline lamellae and amorphous growth ring was caused. All above factors contributed to the decrease of plantain starch resistance to digestion with increasing maturity. This work provides a fundamental understanding of the changes that plantain starch undergoes during ripening. Graphical abstract: Image 10947 Highlights: In vitro digestibility of plantain starch was enhanced with increasing maturity. SEM showed layer-by-layer degradation of the surfaces of plantain starch granules. Crystalline structure of starch changed from CB -type to CA -type using WAXD. SAXS revealed ripening process caused the weakest damage to crystalline region. Our results provide an insight into the changes of plantain starch with ripening.